Simplified Boolean expression for A'BC+AB'C'+A'B'C'+AB'C+ABC
A . AB
B . B'C
C . AB+(A'+AB')C
D . AB'+BC+B'C'
A' BC + AB'C' + A'B'C' + AB'C + ABC
=A' BC + AB'C' + AB'C' + A'B'C' + AB'C + ABC (AB'C' = AB'C '+ AB'C ')
=A' BC + ABC + A'B'C' + AB'C' + AB'C' + AB'C
=BC ( A' + A ) + B'C' ( A' + A ) + AB'( C' + C )
=BC + B'C' + AB'
Hence,Option(D) AB' + BC + B'C' is the correct choice.
Devwritt Your solution is also right.
okay then tell me In 4th line from B'(C'+AC) how did you write B'(C'+A)
B'(C'+AC) = B'(C'+C ) (C'+A) = B'(C'+A)
ANSWER: OPTION D
@Vishal , Its not always true that Most significan bit should be in place of variable C . Point is final output must be valid and correct . So you can do in both way, you can use this way(attached fig) and you'll get the same output . But its good thing Vishal, you can remind and use only one method . But in exam you can't say they will follow your method , right?? So, .focus on basics.